What a farmer should know and be - Harner, Loyall S. (My University, 1892)
Introduction: The importance of the farming industry can hardly be overestimated. Without it no other could exist. In just so far as the industry is important those engaged in it are of importance. Of course natural fruits and wild animals exist in sufficient abundance to support a small population. But dependence on these sources alone for food and raiment makes progress impossible. On the products of the soil is founded the material wealth of a nation. Nowhere has this been more true than in the United States. Since farming is indispensable it follows that the farmer should be one, so far as the power to promote welfare goes, having no superior in the land. He must study and grow in usefulness. His vocation is such that it must be kept to the front. The coming farmer must look ahead, move forward, and not linger along behind the rest of the world. Vigilance and farsightedness are the elements of success.
Citation: Harner, Loyall S. What a farmer should know and be. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Agriculture; Farming; Agronomy; Rural; Theses; Manuscripts (documents)